Knowledge, Acceptance and Application of Islamic Financial Management among Small and Medium Enterprises (SMEs) Halal Entrepreneurs in Peninsular of Malaysia - Daud Awang, Mohd; Muhammad, Junaina; Nur Aiman Mohd Noor, Muhamad; Abdullah, Amalina; Amir Abdullah, Amini; Abdullah, Norsazali; Shobihah Abang Abai, Dayang (KnE Social Sciences, 2020)
The Halal industry in Malaysia has created employment opportunities especially among Small and Medium Enterprises (SMEs). High demand for Halal products especially from Islamic countries has transformed the development of this sector into a national priority. In the Eleventh Malaysia Plan (11MP), the competitiveness of the Halal industry was given special emphasis by the Prime Minister. In Asia, Malaysia has long been considered as a leader in the development of the Halal sector. However, the Halal industry is not only about Halal food production, but also covers Islamic finance services which prohibit interest (riba), uncertainties (gharar) and gambling (maysir). Islamic financial management is one of the important parts of Islamic finance because it plays a big role in providing Shariah-compliant funds and investment opportunities especially for the SME Halal entrepreneur. The holistic approach to the Halal industry should also cover not only food production but also Islamic financial management which includes activities such as how to create, increase, purify and to protect wealth from an Islamic perspective. Therefore, this study examines the relationship between the knowledge and acceptance of Islamic finance, and the application of Islamic financial management among halal entrepreneurs in Peninsular Malaysia. The findings of this study reveal that the knowledge and acceptance of Islamic finance is significantly correlated with the application of Islamic financial management among halal operators of SMEs. This indicates that to integrate the Halal industry with Islamic financial management activities, Halal entrepreneurs should be able to know and accept the Islamic finance principles. This will, in turn, facilitate the promotion of Malaysia’s Halal industries on the global stage. Keywords: Halal Industry, SMEs Halal entrepreneur, Islamic Financial Management